Biological Treatment of Grey Water Using Sequencing Batch Reactor - Rasha K. Sabri (Engineering and Technology Journal, 2013)
The present study included the application of Sequence Batch Reactor SBR technology for the treatment of domestic grey water which represents (50-80%) of the households wastewater. Different cycle times were used 6, 8 & 12 hrs. at each cycle time, The characteristics of (PO4-1, NO3-1, COD) were studied of influent, effluent and through interaction samples in the reactor to evaluate the efficiency of the treatment technology used. It was concluded that removal efficiency of organic matters (COD) increases with increasing the cycle time. Nitrate ( NO3-1 ) removal was dependent on the availability of nutrients for microorganisms. On the other hand, optimum removal of phosphate occurred when aerobic and anoxic periods were equal. when comparing the values characteristics (S.S, pH) for treated grey water with the Iraqi specification, it was found that there was a fair convergence in values. As for the values of electrical conductivity (EC), they were considered suitable for good bearing salts plants according to U.S. Salinity Laboratory classification.